AN ANALYSIS OF SALIENT PROVISIONS OF INTERNATINAL LAW INSTRUMENTS FOR HOLDING PERPETRATORS LIABILE FOR BREACH OF THE DUTY OF CARE TO THE ENVIRONMENT - Walter D. Gaveni; Kola O. Odeku (Perspectives of Law and Public Administration, 2022)
The growing global concern in the perpetration of environmental crimes such as pollution and degradation at an international level by States have triggered massive promulgation of international law instruments to make ample provisions for the protection of the environment and at the same time to impose stringent sanctions to those who harm the environment. The obligation to protect or not to harm the environment has been conceptualized; “the duty to care for the environment” and the International environmental law have made States to also be the bearers of this obligation hence they ought to exercise careness in their daily activities in order to avoid causing harm to the environments in the territory of another State. An act of State done in breach of this obligation is faced with penal consequences which may take civil or criminal form. This paper therefore looks at the salient international instruments or laws that impose liability to States or international organizations who cause environmental harm.